2018
DOI: 10.1007/s00247-018-4146-4
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging in acute pyelonephritis in children

Abstract: Diffusion tensor imaging could replace diffusion-weighted imaging for diagnosis of acute pyelonephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…28 In addition to animal studies, it has been also found that DTI could replace diffusion-weighted imaging for diagnosis of acute pyelonephritis in one study. 29 In the present study, a large proportion of the studied patients presented with AKI which correlated similarly to DTI based on their functional and pathological parameters. This may also suggest a proposed value of renal DTI in evaluation of AKI patients.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…28 In addition to animal studies, it has been also found that DTI could replace diffusion-weighted imaging for diagnosis of acute pyelonephritis in one study. 29 In the present study, a large proportion of the studied patients presented with AKI which correlated similarly to DTI based on their functional and pathological parameters. This may also suggest a proposed value of renal DTI in evaluation of AKI patients.…”
Section: Discussionsupporting
confidence: 52%
“…Diffusion MR metrics were shown to sense flow changes in kidney induced by diuretic challenges suggesting that vascular flow, tubular dilation, water reabsorption and intratubular flow all play important roles in diffusion‐based imaging 28 . In addition to animal studies, it has been also found that DTI could replace diffusion‐weighted imaging for diagnosis of acute pyelonephritis in one study 29 . In the present study, a large proportion of the studied patients presented with AKI which correlated similarly to DTI based on their functional and pathological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The typical findings of acute pyelonephritis using conventional DWI has been described as areas of hindered diffusion [2][3][4][5]. The same findings have been reported using DTI [18]. Multiparametric DTI provides several parameters that can be used for further characterization of these findings.…”
Section: Discussionmentioning
confidence: 62%
“…Recent studies have shown the potential of the technique to evaluate renal pathology in older children [13][14][15][16][17]. It has also been shown that free breathing DTI is feasible and can generate images with higher quality compared to conventional DWI in children with acute pyelonephritis [18]. To our knowledge, there are no studies on renal DTI in young infants, a patient group that would benefit from the use of this noninvasive, non-radiating, short scan technique.…”
Section: Introductionmentioning
confidence: 99%
“…In the acute phase, ADC difference was significant between affected and unaffected tissue and showed excellent discriminatory ability [85]. Other studies confirm the ability of DWI and DTI to detect renal infection in kidneys and diffusion parameters could play an important role in monitoring treatment effectiveness [85][86][87][88]. DWI combined with chemokine receptor CXCR4 targeted positron emission tomography (PET) was able to detect allograft infection, lower UTI and non-urologic infections elsewhere, by the identification of leukocyte infiltration [89].…”
Section: Diffusion Biomarkersmentioning
confidence: 86%